2020
DOI: 10.1002/bmc.4833
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prototypes from Ligustri Lucidi Fructus in rat plasma based on a data‐dependent acquisition and multicomponent pharmacokinetic study

Abstract: The identification and quantization of traditional Chinese medicine (TCM) are a challenge for researchers and industry. Using untargeted analytical methods, the in vivo detection and identification of TCM compounds are difficult because of the significant interference of endogenous substances. Fortunately, the ongoing development of new analytical technologies, especially Q‐Orbitrap–MS, offers some solutions. Our team developed a holistic MS method, combining untargeted data‐dependent MS2 (dd‐MS2) modes to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Nuezhenidic acid, oleoside 11‐methyl ester, 1′''‐ O ‐ β ‐ d ‐glucosylformoside, specnuezhenide, G13, and oleonuezhenide belonged to iridoids. Therein, the pharmacokinetic behaviors of 1′''‐ O ‐ β ‐ d ‐glucosylformoside, specnuezhenide, G13, and oleonuezhenide were quite similar, which was attributed to both of them containing subgroup of phenylethanoid glyosides, which were consistent with the study of researchers [30]. As for oleanolic acid, it showed double peak in plasma concentration–time curve, which was quite common among triterpenoid components.…”
Section: Resultssupporting
confidence: 85%
“…Nuezhenidic acid, oleoside 11‐methyl ester, 1′''‐ O ‐ β ‐ d ‐glucosylformoside, specnuezhenide, G13, and oleonuezhenide belonged to iridoids. Therein, the pharmacokinetic behaviors of 1′''‐ O ‐ β ‐ d ‐glucosylformoside, specnuezhenide, G13, and oleonuezhenide were quite similar, which was attributed to both of them containing subgroup of phenylethanoid glyosides, which were consistent with the study of researchers [30]. As for oleanolic acid, it showed double peak in plasma concentration–time curve, which was quite common among triterpenoid components.…”
Section: Resultssupporting
confidence: 85%
“…Several studies have investigated the pharmacokinetics and distribution of active components of LLF in rats [ 30 , 31 , 32 , 33 ]. The pharmacokinetic properties of LLF indicated that LLF compounds can be better absorbed by the blood and maintained for a long period of time [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the pharmacokinetics and distribution of active components of LLF in rats [ 30 , 31 , 32 , 33 ]. The pharmacokinetic properties of LLF indicated that LLF compounds can be better absorbed by the blood and maintained for a long period of time [ 30 ]. Additionally, the UPLC-MS method was used to study the pharmacokinetics of salidroside in control and ovariectomized rats; the results demonstrated that the t1/2, MRT0–∞, and apparent volume of distribution for salidroside increased in ovariectomized rats compared with control rats [ 31 ].…”
Section: Introductionmentioning
confidence: 99%